2013
DOI: 10.2478/v10184-012-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of major isoflavones in Glycine max L. through the elicitor-mediated approach

Abstract: -Isoflavone content in soybean seeds was enhanced by the elicitor-mediated approach under field conditions through the floral application of abiotic elicitors-salicylic acid, methyl jasmonate and biotic elicitors-Aspergillus niger and Rhizopus oligosporus. Among isoflavones, daidzein and glycitein were found to be highly responsive to elicitors, with an increase of 53.7% and 78.7%, respectively as compared to control. Highest total isoflavone content (1276.4 mg g -1 of seeds) was observed upon the administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The previous studies reported that Saccharomyces enhanced the production of secondary metabolites to a great extent . Signaling molecules, including jasmonic acid (JA), salicylic acid (SA) and nitric oxide (NO), were previously studied for their effects on plants and microorganisms . JA signaling pathway plays a role as transducer in accumulating the secondary metabolites in THE treatment group .…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported that Saccharomyces enhanced the production of secondary metabolites to a great extent . Signaling molecules, including jasmonic acid (JA), salicylic acid (SA) and nitric oxide (NO), were previously studied for their effects on plants and microorganisms . JA signaling pathway plays a role as transducer in accumulating the secondary metabolites in THE treatment group .…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous application of 25 ppm methyl jasmonate (MJ) and salicylic acid (SA) was also shown being beneficial for enhanced production of carotenoids through differential regulation (more than 6-fold up-regulation) of carotenoid biosynthetic genes in red algae ( Various biotic and abiotic elicitors have been used in fruits and vegetables at preharvest and post-harvest stages for quantitative enhancement of bioactive compounds, antioxidant activity and economic yield (Baenas, et al, 2014;Saini, et al, 2013); however information about functional efficiency of elicitors is scare. Thus, the effect elicitors on bioaccessibility and bioavailability of health promoting compounds should be analyzed to justify the functional benefits of elicitation.…”
mentioning
confidence: 99%
“…Numerous factors influence the isoflavone content in the soybean varieties: growth stage, planting location, variety, cropping year, climate, country of origin, and seed weight etc., and all factors might contribute for alteration in the isoflavone levels in soy varieties (Riedl et al 2007;Sakthivelu et al 2008;Saini et al 2013;Zhang et al 2014). Similarly, major differences in the levels of individual isoflavones were observed within the three soybean cultivars viz., Hrvatica, Lea, Danica from Croatia, wherein, TI content ranged from 80.7 to 213.6 mg/100 g of soybean, with genistein as the most abundant isoflavone (Mujić et al 2011).…”
Section: Isoflavone Analysismentioning
confidence: 89%